Impact of multiple consultations and switching in treatment-seeking in tuberculosis: Mathematical modelling and optimal control - Preeti Saini; Samit Bhattacharyya (PLoS ONE, 2025)
Treatment-seeking behaviour significantly contributes to the worldwide tuberculosis (TB) burden, especially in Southeast Asia and African regions. At the onset of symptoms like coughing, fever, fatigue, and loss of appetite, individuals visit various clinics or alternative medicine centres, often switching multiple times before actually reaching a TB DOTS (Directly Observed Therapy Short Courses) centre. This, however, introduces a long delay in proper diagnosis and treatment of TB cases, which increases community transmission and the overall TB burden. By synthesizing data from various empirical studies, we develop an intricate mathematical model of such multiple consultations and aim to quantify the impact of such behavioural interactions on disease burden. Our SIR-based TB transmission framework quantifies the rise in active TB cases due to delays from multiple consultations before diagnosis and treatment at DOTS centres. We found that up to 2-3 consultations before diagnosis can substantially lower the overall TB burden. Using optimal control modelling, we propose targeted interventions – including enhanced TB awareness, early detection, and improved healthcare infrastructure. These findings offer valuable insights for policymakers and public health organizations to develop effective strategies for TB control in high-prevalent regions.